2008
DOI: 10.1111/j.1365-3164.2008.00675.x
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse effects of ketoconazole in dogs – a retrospective study

Abstract: Although ketoconazole has been used extensively in dogs for the treatment of various fungal infections, information about adverse effects is mainly anecdotal. Common adverse effects in humans include dose-dependant anorexia, nausea and vomiting, allergic rashes and pruritus. Drug-induced hepatitis is very rare, but potentially fatal. The aim of this study was to evaluate the type and frequency of adverse effects associated with ketoconazole therapy in dogs treated for skin diseases and any possible influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
0
19
2
1
Order By: Relevance
“…Although a recent retrospective analysis of the adverse effects of KTZ in dogs did not indicate that dose was a factor in the number or severity of adverse effects for KTZ, it has been shown that vomiting occurred more often with co-administration of CSA and KTZ. 7,33 Vomiting in the present study, however, occurred more frequently during Treatment 1. Additionally, inhibition of the CYP 450 enzymes by KTZ has been shown to be dose dependent, which was supported in the present study, with blood and skin CSA concentrations obtained in Treatment 3 being higher than those in Treatment 4.…”
Section: Discussioncontrasting
confidence: 49%
“…Although a recent retrospective analysis of the adverse effects of KTZ in dogs did not indicate that dose was a factor in the number or severity of adverse effects for KTZ, it has been shown that vomiting occurred more often with co-administration of CSA and KTZ. 7,33 Vomiting in the present study, however, occurred more frequently during Treatment 1. Additionally, inhibition of the CYP 450 enzymes by KTZ has been shown to be dose dependent, which was supported in the present study, with blood and skin CSA concentrations obtained in Treatment 3 being higher than those in Treatment 4.…”
Section: Discussioncontrasting
confidence: 49%
“…Although the margin of safety for CSA administration in canines is much greater than that in humans, adverse effects from CSA have generally been observed to be dose dependent, supporting the importance of using the lowest effective dose. Although a recent retrospective analysis of the adverse effects of KTZ in dogs did not indicate that dose was a factor in the number or severity of adverse effects for KTZ, it has been shown that vomiting occurred more often with co‐administration of CSA and KTZ 7,33 . Vomiting in the present study, however, occurred more frequently during Treatment 1.…”
Section: Discussioncontrasting
confidence: 84%
“…When higher daily doses are used then a further increase by 0.1 mg/kg/day is recommended. Other P‐glycoprotein inhibitors, such as ketoconazole or ciclosporin, if given concurrently, increase the likelihood of adverse effects (COE III) 55,56 …”
Section: Treatment Of Canine Demodicosismentioning
confidence: 99%
“…Other P-glycoprotein inhibitors, such as ketoconazole or ciclosporin, if given concurrently, increase the likelihood of adverse effects (COE III). 55,56 More recently, an ABCB1-D1 (MDR-1) mutation considered responsible for the acute toxicity in collie dogs and several other herding breeds has been identified. [57][58][59] Testing for this defect is possible.…”
Section: Ivermectinmentioning
confidence: 99%